Radiocarbon age constraints for a Pleistocene–Holocene transition rock art style: The Northern Running Figures of the East Alligator River region, western Arnhem Land, Australia. (February 2017) - Jones, Tristen; Levchenko, Vladimir A; King, Penelope L.; Troitzsch, Ulrike; Wesley, Daryl; Williams, A Alan; Nayingull, Alfred
Abstract: In this article we present nine radiocarbon age determinations producing a minimum age and a minimum age range for a regionally distinct rock art style known as the Northern Running Figures from Red Lily Lagoon, western Arnhem Land Australia. These radiocarbon determinations provide age constraints for both Pleistocene and early Holocene rock art in western Arnhem Land. The radiocarbon age determinations are produced from extracting calcium oxalate contained within mineral crusts associated with the rock art. Significantly this study employs a novel separation technique, designed to effectively isolate the oxalate compounds from the mineral crust sample using chemical pre-treatment, and demonstrates significant time offsets between radiocarbon age determinations for the calcium oxalates and other carbon inclusions contained within mineral crusts. Highlights: Nine radiocarbon age determinations for a regional rock art style in Australia are reported. The radiocarbon determinations provide age constraints for Pleistocene and early Holocene rock art. The radiocarbon ages are produced from extracting calcium oxalate contained within mineral crusts. A novel chemical pre-treatment separation technique for the radiocarbon dating method is employed.